SOX6 suppresses the development of lung adenocarcinoma by regulating expression of p53, p21CIPI, cyclin D1 and β‐catenin - Liyan Lv; Min Zhou; Jian Zhang; Fang Liu; Li Qi; Shuai Zhang; Yi Bi; Yan Yu (FEBS Open Bio)
The Sry‐related high‐mobility group box6 (SOX6) has been implicated in the development of cancer, but its role in lung cancer is incompletely understood. Here, we report that SOX6 expression is frequently down‐regulated in lung adenocarcinoma tissues. Moreover, SOX6 can inhibit the proliferation and invasion of lung adenocarcinoma cells, which may occur through cell cycle arrest at G1/S due to up‐regulation of p53 and p21CIPI and down‐regulation of cyclin D1 and β‐catenin. Univariate and multivariate analyses revealed that the expression of SOX6 is significantly associated with patient disease‐related survival and is an independent prognostic factor for lung adenocarcinoma. These data suggest that SOX6 may act as a suppressor of lung adenocarcinoma.